Potential role of extracellular granzyme B in wet age-related macular degeneration and fuchs endothelial corneal dystrophy - Dubchak, Eden; Obasanmi, Gideon; Zeglinski, Matthew R.; Granville, David J.; Yeung, Sonia N.; Matsubara, Joanne A. (Frontiers in Pharmacology, 2022)
Age-related ocular diseases are the leading cause of blindness in developed countries and constitute a sizable socioeconomic burden worldwide. Age-related macular degeneration (AMD) and Fuchs endothelial corneal dystrophy (FECD) are some of the most common age-related diseases of the retina and cornea, respectively. AMD is characterized by a breakdown of the retinal pigment epithelial monolayer, which maintains retinal homeostasis, leading to retinal degeneration, while FECD is characterized by degeneration of the corneal endothelial monolayer, which maintains corneal hydration status, leading to corneal edema. Both AMD and FECD pathogenesis are characterized by disorganized local extracellular matrix (ECM) and toxic protein deposits, with both processes linked to aberrant protease activity. Granzyme B (GrB) is a serine protease traditionally known for immune-mediated initiation of apoptosis; however, it is now recognized that GrB is expressed by a variety of immune and non-immune cells and aberrant extracellular localization of GrB substantially contributes to various age-related pathologies through dysregulated cleavage of ECM, tight junction, and adherens junction proteins. Despite growing recognition of GrB involvement in multiple age-related pathologies, its role in AMD and FECD remains poorly understood. This review summarizes the pathophysiology of, and similarities between AMD and FECD, outlines the current knowledge of the role of GrB in AMD and FECD, as well as hypothesizes putative contributions of GrB to AMD and FECD pathogenesis and highlights the therapeutic potential of pharmacologically inhibiting GrB as an adjunctive treatment for AMD and FECD.